Development of the Ambulance 3.0 platform application - A. Z. Barybina (Вестник университета)
The article examines the application of the platform approach to solving the problem of optimizing the work of emergency medical services in the city of Yekaterinburg with a population of over a million. This project is especially relevant due to the ambulance operators and crews’ heavy workload associated with seasonal increases in the morbidity rate, the COVID-19 pandemic and other crisis situations. The goal of the study is to solve the aforementioned problems by means of developing a highly specialized but also functional service as well as ensure the possibility of using it in the post-pandemic era. The author of the article points out that current realities make it especially important to create such application because while relevant Russian studies do not pay proper attention to emergency medical services issues, the use of foreign counterparts is not possible for various reasons, including that of the large amount of confidential data that require processing. It is expected that in case the technical and software parts of the project are implemented successfully, the application described in the study will allow to achieve all the objectives set and ensure the improvement of the socio-economic situation of Yekaterinburg.